Families in motion : ebbing and flowing through space and time - Murray, Lesley; McDonnell, Liz; Hinton-Smith, Tamsin; Ferreira, Nuno; Walsh, Katie (Bingley, U.K. : Emerald Publishing Limited, 2019)
This interdisciplinary edited collection will challenge the idea of the static family that can be 'broken', and instead think of family as always 'on the move', both conceptually and in practice. This dual approach to family is the unique contribution of the book, which offers new perspectives on the sociology and geography of the family, drawn together by the shared lens of family mobilities. As such it brings together insights from the diverse work of interdisciplinary academics working alone and collaboratively on different aspects of family lives and relationships. The central argument of the book is that the concept of family is always in motion: a disruption in one aspect of family relations, for example, the ending of the intimate relationship between parents, is part of the ongoing project of family. In addition, families are made through mobility and immobility in relation to people, communications, objects and ideas. Contributions from a range of academics across disciplines consider changes in family practices and the ways in which they are produced through motion. This book seeks to understand families as always in motion; changing, adapting and re-routed. Integral to this discussion is the spatiality and temporality of family, that families are produced in different times and spaces. Families are also made through interactions with material things, including non-human living things and through the emotional ties and responses that determine their form and practices.
1. Introduction / Lesley Murray, Liz McDonnell, Katie Walsh, Nuno Ferreira, and Tamsin Hinton-Smith -- Section 1: Moving through separation and connection -- 2. Travelling feelings : narratives of sustaining love in two comparative cultural case studies of fathering during family separations / Alexandra Macht -- 3. 'Clinging on' : prison and the changing landscape of the family / Marie Hutton 4. 'Living together apart' as families in transition / Liz Mcdonnell, Lesley Murray, Tamsin Hinton-Smith and Nuno Ferreira -- 5. 'The sense of space' of children living in stepfamilies in Belgium / Laura Merla and Bérengère Nobels -- Section 2: Uneven motions and resistance -- 6. The roles of ICTs in sustaining the mobilities of transnational families / Sondra Cuban -- 7. Life course transitions as liminal zones / Bella Marckmann -- 8. Jumping through hoops : families' experiences of pre-birth child protection / Ariane Critchley -- 9. Families and flow : the temporalities of everyday family practices / Clare Holdsworth -- Section 3: Traces and potentialities -- 10. losing a father in a demolished ex-industrial landscape : a researcher's emotional geography / Lisa Taylor -- 11. Children in motion : doing family across two households / Rakel Berman -- 12. Families on-foot : assembling motherhood and childhood through care and play / Susannah Clement -- 13. Reconciling past family disruption and transitional flux into the present : foster care-experienced youths' parenting narratives / Caroline Cresswell -- 14. Moving to be a family : the case of italian women in Morocco / Maria Giovanna Cassa.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Families; Human geography; Social Science -- Sociology / Marriage & Family; Sociology: family & relationships